Diseño de una plataforma de interconexión para evaluación de un circuito integrado en alta frecuencia para espectroscopía de impedancia eléctrica - Chavarría-Zamora, Luis Alberto (Instituto Tecnológico de Costa Rica, 2016)
An initiative is being developed between TUHH (Technische Universit at Hamburg-Harburg) and ITCR (Instituto Tecnol ogico de Costa Rica), its goal is to analyze biological samples through the EIS (Electrical Impedance Spectroscopy) method. An IC(Integrated Circuit) will be made to perform these analyses up to 10GHz, and to check its functionality in this frequency range, on a preliminary stage a interconnection platform will be made. In this job will be seen the design process and simulations that would allow to reach a functional and optimal platform for the chip. Tests will be made to verify the signal integrity at top frequencies in electromagnetic simulation software.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Electrónica, 2016.
Keywords: Tecnología; Señales; Electromagnetismo; Simulación; Plataforma; Interconexión; Frecuencia; Radiofrecuencia; Conectores